Factors affecting women in acquiring leadership positions in workplaces: A human resource management perspective - Mwita, Kelvin M; Mwakasangula, E (2024)
A research paper submitted to the Social Sciences, Humanities and Education Journal (SHE Journal), Volume 4 (1) of January 2023, pg. 20 – 31,